SIMULASI VLAN DAN ETHERCHANNEL DENGAN MENERAPKAN PROTOKOL INTERNET VERSI 6 (IPV6) - , IKA RUSSINTA, Sri Suning Kusumawardani, S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The background of this research is the problems that arise on a switch networks Local Area Network (LAN) which is broken link connection. When the damage occurs then the currently running process will be hampered. Therefore, it is necessary that the network is stable and has a system that allows the network continues to run smoothly although the link connection is broken. Etherchannel is trunking technology that allows bundling of several devices physical port to create a single logical link into one port group. The purpose of this research is to create a switches network with high speed connections and reliable. The network should also be able to keep it running smoothly despite one of the lines used damaged. The research was conducted by designing the topology of the apparent corporate LAN called Good Oil using different VLAN for each department according do its function and implementation of Internet Protocol version 6 addresses (IPv6). VLAN technology used because its function of switches network. In the topology will be used Etherchannel technology on each switch to provide a backup link. The topology is designed using Packet Tracer 6.0.1 software using the principle of hierarchical topology. At the final stage of the study, performed the simulation and analysis to look at the results that occur. Based on the simulation and analysis are carried out, it can be concluded that the network topology switches with VLAN and Etherchannel IPv6 implementation goes well. Testing of connectivity from any end Services has successfully done. Networks become reliable and have high bandwidth scales. In Etherchannel configuration speed, duplex mode, VLAN, and the range of allowed VLANs on both sides must be equal and configured in trunk mode. Port Channel contained in the Networks, can still work using other ports when one port is broken, using Etherchannel technology.